Short-term evaluation of hypertonic dextrose prolotherapy intra-articular injection on femoral cartilage thickness among Knee Osteoarthritis Patients with Obesity - Pane, Rita Vivera; Aisyah; Handayani; Al Hajiri, Aufar Zimamuz Zaman (UNUSA Press, 2024)
Introduction: The impact of obesity greatly influences morbidity rates and leads to increase the risk of knee osteoarthritis (KOA). Objective: This study aimed to evaluate the short-term effect of intra-articular injection of hypertonic dextrose prolotherapy (HDP) on femoral cartilage (FC) thickness among KOA with obese patients. Methods: This is a quasi-experimental clinical trial study. KOA patients with obesity registered from May to August 2023 in the Department of Physical Medicine and Rehabilitation (PM&R) RSUD Haji Provinsi Jawa Timur, Surabaya, Indonesia. The intervention group received an HDP injection, while the control group received a normal saline (NS) injection. The FC thickness was scanned with musculoskeletal ultrasound (US) before the intervention, 2 weeks, and 6 weeks after intervention. Mean difference within-group and intra-group was analyzed statistically with a significant value of P < 0.05. Results: 38 participants who were diagnosed with KOA and obesity were involved in this study. The FC thickness before intervention in the NS group at the LC, IC, and MC sites was 1.47 ± 0.45 1.23 ± 0.47 1.33 ± 0.49 mm, respectively, while in the HDP group it was 1.57 ± 0.70 1.38 ± 0.65 1.33 ± 0.61 mm. Within-group analysis of each group from pre-intervention until 6 weeks using repeated measurement ANOVA showed significant values in the HDP group at all sites, including LC, IC, and MC, with each value P < 0.05. Conclusions: The short-term effect of HDP injection is beneficial in increasing FC thickness in KOA with obese patients.